2018
DOI: 10.1038/s41598-018-33736-w
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical and Radiological Experience with a Ceramic Bone Graft Substitute in the Treatment of Benign and Borderline Bone Lesions

Abstract: Substitutes for bone grafts experience increasing popularity, but the need for defect-filling following simple curettage of benign bone lesions is controversial. In this study, we wish to objectively report the radiological changes following bone defect-filling using a composite ceramic bone graft substitute, as well as the clinical results and complications. We evaluated 35 surgically treated benign bone lesions with subsequent defect-filling using two variants of a composite ceramic bone graft substitute (CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In the present study, all preoperative pathological fractures were healed within 3 months after tumor resection followed by UDPHAp implantation, and 84% of cortical thinning around the tumor was regenerated at a mean of 10 months postoperatively. Horstmann et al 1 reported similar cortical bone thickness results using a composite ceramic bone graft substitute. There have been few other studies on postoperative radiographic change in cortical thinning due to bone tumors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the present study, all preoperative pathological fractures were healed within 3 months after tumor resection followed by UDPHAp implantation, and 84% of cortical thinning around the tumor was regenerated at a mean of 10 months postoperatively. Horstmann et al 1 reported similar cortical bone thickness results using a composite ceramic bone graft substitute. There have been few other studies on postoperative radiographic change in cortical thinning due to bone tumors.…”
Section: Discussionmentioning
confidence: 87%
“…Tumor resection often results in more severe cortical bone thinning. Horstmann et al 1 studied postoperative changes of cortical thinning in the treatment of benign bone tumors, and reported that cortical thickness normalized in 80% of cases one year after tumor resection and filling with bone substitutes. It is important to fill the cavity left after intralesional resection to restore mechanical strength, although it depends on the size of the defect, the anatomical location, and the functional demands and expectations of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Horstmann et al reported an 11% (4 of 35 cases) risk of benign rumor recurrence within 16 months. However, they reported that the rate of product resorption did not influence the indication for reoperation [3].…”
mentioning
confidence: 96%
“…Iundusi et al reported graft material resorption within 3-8 months in a series of 24 tibial plateau fractures in which CERAMENT was utilized [5]. Horstmann et al reported near complete graft material resorption after 1 year when CERAMENT was used in the treatment of benign and borderline bone lesions [3]. Likewise Kaczmarczyk et al reported complete graft material resorption within 12 months in 13 out of 14 benign bone tumors in which CERAMENT was utilized in management [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation